Pembelajaran Diferensiasi dan STEAM dengan Metode Ecobrick untuk Meningkatkan Potensi Siswa Kelas 2 A SD Negeri 1 Waringinsari - Fatihah, Melani Dewi (Jurnal Didaktika Pendidikan Dasar, 2024)
The STEAM approach is an innovation discovery procedure that prioritizes process skills. At SD Negeri 1 Waringinsari, rubbish has been piling up in a corner of the elementary school for years, some of which is plastic waste. One way to process plastic waste is to make crafts by recycling plastic waste into ecobricks or into toys such as cars. The results of this research show that the application of differentiation and STEAM learning models by making ecobricks and recycling bottle waste can increase the potential of class 2A students. at SD Negeri 1 Waringinsari, Banjar City, West Java, in making works in the form of cars. Student learning outcomes at the end of learning meeting 3 increased from the previous 84.40 to 88.60, the skill score (project) to make the work of processing plastic waste into cars had a class average of 85.47 and the design was in the good category.